The evolution of audiovisual news in the opinion of its creators: from on-demand television to vodcasting - Moreno-Espinosa, Pastora (2021)
While until now news programmes have been designed to be broadcast on large screen formats, especially television and computer screens, for the last decade, programmers have been making efforts to reach consumers on smaller receiver formats such as tablets and, more recently, mobile phones. Faced with this reality, television news has been redefined and reoriented, even using non-professional images for broadcasting. In this article, we review the evolution of audiovisual news, from television news to on-demand television and from there, its transition to vodcasting; all of this through an updated bibliography and the vision of television news managers. We therefore use a qualitative, descriptive and exploratory methodology, applying a questionnaire as a methodological tool. Audiovisual information has always been the most consumed and has increased with situations such as the global pandemic of the COVID-19 disease. According to a report by the Barlovento Comunicación consultancy published in June 2020, audiovisual consumption in Spain grew by 22%, both through conventional television and the Internet. The management of over-information and its adaptation to new consumption environments must be a maxim for journalistic content managers. Our study concludes, among other things, that although the forms of consumption have changed considerably and television news managers believe that they must adapt to them, so far content has been adapted to these new formats, but little material is produced expressly for video podcasting or vodcasting platforms in our country.